Effect of phthalocyanine, methylene blue and toluidine blue photosensitizers on the adhesive interface of fiber posts: a confocal laser microscopy study - Gok, Tuba; Karaoglu, Gamze Er; Korucu, Hulde (Springer London Ltd, 2025)
Phthalocyanine (Pc) is a promising photosensitizer for photodynamic therapy (PDT), offering advantages such as high light stability, strong absorption, efficient singlet oxygen production, and low dark toxicity. This study evaluated the effects of PDT with different photosensitizers on the penetration depth and area of self-adhesive resin cement into dentinal tubules. Forty single-canal, round-shaped lower premolar teeth were prepared using the ProTaper Next system. After root canals were filled with the single cone technique, samples were stored for 7 days. Post spaces were created, and samples were divided into four groups: control, methylene blue (MB), toluidine blue (TB), and Pc groups. PDT was performed using photosensitizers combined with light-emitting diodes (LEDs). 1.0 mm +/- 0.1 axial sections were taken from the 1, 5, and 8 mm levels from the orifice. The penetration depth and area of self-adhesive resin cement into dentinal tubules were analyzed using a confocal laser microscope. Statistical analyses were conducted using ANOVA and Tukey's test. Cement penetration depth decreased from coronal to apical sections in all groups. At the 1 mm level, MB showed a greater penetration area than Pc, while at the 5 mm level, MB showed a lower penetration area than the control group (p < 0.05). No significant differences were found at the 8 mm level. This study showed that while adhesive penetration depth did not differ significantly among groups, penetration area varied at 1 mm and 5 mm sections. Methylene blue exhibited a higher penetration area at 1 mm compared to phthalocyanine, whereas toluidine blue showed consistent penetration across sections. In terms of penetration depth and area findings, the findings showed that PC can be used as an alternative photosensitizer in PDT application in endodontics, showing generally similar findings with MB and TB.
Keywords: Adhesive interface; Confocal laser microscopy; Dentin tubule penetration; Fiber post; Photodynamic therapy; Photosensitizer